Monolithic microwave duplexer (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2009)
The results of development monolithic dielectric duplexer with the increased attenuation between channels are given, that is achieved asymmetric amplitude-frequency characteristics of the channel filters.